Pengaruh Financial Distress, Komisaris Independen, Kepemilikan Institusional, Audit Tenure, dan Reputasi KAP Pada Ketepatwaktuan - Pramesti, Ni Made Manik Dwi; Suputra, Dewa Gede Dharma (E-Jurnal Akuntansi; Vol 26 No 2 (2019)DO - 10.24843/EJA.2019.v26.i02.p02, 2019)
This study aims to determine the effect of financial distress, independent commissioner, institutional ownership, audit tenure and reputation of public accounting firm on the timeliness of publication of financial statements.This research was conducted at a manufacturing company listed in Indonesia Stock Exchange (BEI) period 2014-2016. The number of samples of 65 companies with 195 observations that meet the criteria of research by using purposive sampling method.Data analysis technique used is logistic regression analysis. The results of the analysis found that financial distress and independent commissioners had a positive effect on the timeliness of the publication of financial statements, while institutional ownership, audit tenure, and reputation of public accounting firms did not affect the timeliness of the publication of the financial statements.   Keywords : financial distress, independent commissioner, institutional   ownership, audit tenure, reputation of KAP,  timelinesss.